Prediction criteria of lethal outcome of acute recurrent cerebral ischemic hemispheric stroke - Novikova, L. V.; Новікова, Любов Вікторівна; Kozyolkin, O. A.; Козьолкін, Олександр Анатолійович (Запорізький державний медичний університет, 2019)
Background. An early and reliable prognosis of stroke outcome is extremely important for initiation of individual treatment as well as for rehabilitation options. Aim. This work aimed to develop criteria for the prediction of acute recurrent cerebral ischemic hemispheric stroke (RCIHS) outcome based on comprehensive clinical, laboratory and neuroimaging investigations. Materials and Methods. The study included 136 patients with acute RCIHS, among them 111 adults (62 males and 49 females, median age 72.0 (64.0; 77.0) were survived and 25 patients (9 males and 16 females, median age 76.0 (74.0; 78.0) died within first 21 days of disease. All patients underwent a detailed clinical and neurological assessment using National Institutes of Health Stroke Scale (NIHSS), brain computed tomography and laboratory examinations. The univariate and multivariate regression analysis were used to find out dependent and independent risk factors associated with lethal outcome (LO) of RCIHS. The predictive value of the indicators was evaluated using ROC analysis with calculation of sensitivity and specificity.
Keywords: тези доповідей